Religious Communication of Sunni-Shi'i in Resolving Internal Religion Conflict in North Sumatra - Hasyimsyah Nasution; Suwardi Lubis; Abdul Khalik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to find and study about model religious communication and Sunni-Syi'i Conflict in Social Media in Making Harmonist Relationships in North Sumatera. This research will start from the interpretive paradigm. In this paradigm view, human beings are "impossible not to communicate". The result shows that Since the beginning of their respective existence, religious communication between Sunni-Shi'is in North Sumatra has always experienced ups and downs in accordance with the existing context in the region. Following the fatwa from the Center, all Islamic organizations in North Sumatra, both NU, Muhammadiyah and Al Washliyah as the oldest Islamic organizations, as well as more recent Islamic organizations such as An Nas, which are Sunnah, agree to state that Shi'ism is a religious understanding who are perverted / deviant. However, based on existing political trends, after the Reformation, slowly the views of Sunni Islamic Organizations began to shift. This shift in view also follows the fatwa of the leadership of the mass organizations at the central level, along with the constellation of religious relations in the Islamic world, even though the shift is taking place gradually. The more moderate NU argues that the non-ghulat Syi groups are not heretical, even though grassroots congregations still view all Shi'i ideas as deviant / deviant, because information does not spread quickly and evenly.